The Canadian International Medical Graduate Bottleneck: A New Problem for New Doctors (Canadian Medical Education Journal, 2011)
Background: A growing population of Canadian students are travelling outside of Canada for medical training. The purpose of this study is to assess the opportunity for Canadians studying medicine abroad (CSAs) to secure post-graduate medical residency positions as International medical graduates (IMGs) in Canada.Methods: Current statistics on IMG applicants into the Canadian Residency Matching Service (CaRMS) will be compared to the number of CSAs applying to return to Canada.Results: In 2010, 75% (1232) of IMG applicants were unmatched following application to CaRMS, despite a doubling in positions reserved for IMGs from 2003. An estimated 3750 CSAs are currently attending over 55 medical schools globally; a six-fold increase since first reports in 2006. Between 2012 and 2014, it is estimated that 72.8% of CSAs will graduate, with 90.4% hoping to return to Canada for post-graduate residency training.  Discussion: The increasing population of CSAs poses a significant risk for future IMGs attempting to secure postgraduate training positions in Canada. From this perspective, we have coined the term ‘Canadian IMG Bottleneck’ – which describes the funnelling effect that has been created by the growing number of CSAs and the limited number of IMG residency positions available in Canada.